2023
DOI: 10.1073/pnas.2219339120
|View full text |Cite
|
Sign up to set email alerts
|

A genetically encoded photoproximity labeling approach for mapping protein territories

Abstract: Studying dynamic biological processes requires approaches compatible with the lifetimes of the biochemical transactions under investigation, which can be very short. We describe a genetically encoded system that allows protein neighborhoods to be mapped using visible light. Our approach involves fusing an engineered flavoprotein to a protein of interest. Brief excitation of the fusion protein leads to the labeling of nearby proteins with cell-permeable probes. Mechanistic studies reveal different labeling path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The work described here further enriches the toolbox for RNA proximity labeling while the concept of orthogonal labeling lays a solid foundation for multidimensional analysis of RNA dynamics. During the process of our study, Muir and co-workers employed the flavin mononucleotide binding protein domain (a mutant of an Arabidopsis thaliana phototropin, termed as LOV*) to achieve proximity labeling with BP and biotin-aniline (BA) under blue light illumination, where both BP and BA displayed the robust protein labeling efficacy via the single electron transfer pathway, while BA also worked well in the 1 O 2 -dependent manner . Taking together our data shown in Figure A, we believe that the pathway selection probably relies on the local environment, as well as the nature of the diverse chemical and genetically encoded photosensitizers.…”
Section: Discussionmentioning
confidence: 79%
“…The work described here further enriches the toolbox for RNA proximity labeling while the concept of orthogonal labeling lays a solid foundation for multidimensional analysis of RNA dynamics. During the process of our study, Muir and co-workers employed the flavin mononucleotide binding protein domain (a mutant of an Arabidopsis thaliana phototropin, termed as LOV*) to achieve proximity labeling with BP and biotin-aniline (BA) under blue light illumination, where both BP and BA displayed the robust protein labeling efficacy via the single electron transfer pathway, while BA also worked well in the 1 O 2 -dependent manner . Taking together our data shown in Figure A, we believe that the pathway selection probably relies on the local environment, as well as the nature of the diverse chemical and genetically encoded photosensitizers.…”
Section: Discussionmentioning
confidence: 79%
“…[ 18 ] Importantly, different from previous reports, histidine was not top‐ranked in P5 enabled proximity labeling (Figure 4I ; Figure S20 , Supporting Information). [ 19 ] Interestingly, by comparing the grand average of hydropathicity (GRAVY) of labeled peptides and full‐length proteins, we observed that these labeling sites in all three model proteins were predominantly located in the hydrophobic peptide region (Figure 4J ; Tables S3–S5 , Supporting Information). This result further supported the hypothesis that the hydrophobic effect governs P5's binding to aggregated proteins (Figure 2G ; Table S1 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Phenol derivatives have been widely used in APEX-mediated labeling by forming reactive phenol radicals ( 18 , 46 ). A genetically encoded photosensitizer has achieved RNA proximity labeling with phenol biotin ( 20 , 47 ). To evaluate the feasibility of phenol radicals on RNA proximity labeling mediated by FAP–MG-HI, dot blot analysis was conducted with phenol alkyne (PhA) ( 46 ) in comparison to PA. As shown in Figure 2F , PhA-tagged RNA exhibited a much lower signal than that of PA, and the weak labeling signal of PhA was further quenched by adding NaN 3 .…”
Section: Resultsmentioning
confidence: 99%